Penerapan Sustainable Food System pada Kelompok Tani di Desa Batur - Skolastika Olivia Puspita; Theresia Pratiwi Elingsetyo Sanubari; Firdhan Aria Wijaya (Amerta Nutrition, 2022)
Background: Recently, the increase in population and the shift in food consumption patterns has affected the whole food production system. In addition, it encourages the government to implement imports, which causes a fluctuation of food prices and can affect food vulnerability for the poor. Most of the population in Indonesia live as farmers in the countryside. Some of them tend to struggle because of the uncertainty of food production which is caused by the limitations of natural resources, climate change, and natural disasters. Consequently, it makes them food insecure. Some of the farmers have already employed organic horticultural agriculture. It means indirectly they have already applied a sustainable food system that has a positive impact on three-dimensional aspects: economic values, social benefits, and environmental sustainability. Objectives: The purpose of this study is to determine the extent to which farmers have implemented a sustainable food system. Methods: With the qualitative method, this research uses Focus Group Discussion (FGD) and in-depth interviews approach to find out the opinions of participants on implementing a sustainable food system. Results: It can be confirmed from this research that all of the participants have applied the sustainable food system (SFS) theory from their own perspectives. They consider using less chemical fertilizer and pesticides, sharing information about how to manage pests, fungus, and diseases among the farmers; and using the intercropping method. Based on those activities, they construct their own sustainability. Conclusions: The conclusion from this study found that participants have implemented SFS in different ways, although the SFS theory carried out by research participants has the same goal, namely for sustainability for future generations.